2012
DOI: 10.1177/2047487312444368
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic incompetence predicts impaired response to exercise training in heart failure patients with sinus rhythm

Abstract: The presence of impaired chronotropic competence is a major predictor of poor training response in CHF patients with sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 29 publications
4
36
0
4
Order By: Relevance
“…Several studies suggested that a poor exercise‐induced HR response is an independent predictor of worse outcomes in several cardiovascular diseases , as well as in an apparently healthy population . Although the specific underlying mechanisms are far from being elucidated, this clinical feature has been attributed—in systolic HF patients—to a reduced myocardial sensitivity to sympathetic modulation together with a beta‐receptor down‐regulation, as well as to the anatomical and electrophysiological changes in the properties of the sinus node .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that a poor exercise‐induced HR response is an independent predictor of worse outcomes in several cardiovascular diseases , as well as in an apparently healthy population . Although the specific underlying mechanisms are far from being elucidated, this clinical feature has been attributed—in systolic HF patients—to a reduced myocardial sensitivity to sympathetic modulation together with a beta‐receptor down‐regulation, as well as to the anatomical and electrophysiological changes in the properties of the sinus node .…”
Section: Discussionmentioning
confidence: 99%
“…The poor response to rehabilitation in a subgroup of patients does not seem to be COPD-specific and/or rehabilitation-specific. Indeed, also subgroups of patients with chronic neurological diseases [35], chronic cardiac diseases [36], or chronic musculoskeletal diseases [37] respond poorly to specialised rehabilitative interventions. Moreover, response to pharmacological therapy [38,39], ambulatory oxygen therapy [40], bronchoscopic interventions [41] and lung volume reduction surgery [42] is also poor in subgroups of patients with COPD.…”
Section: Poor Response To Pulmonary Rehabilitationmentioning
confidence: 99%
“…The contribution of stroke volume to cardiac output at high altitude is therefore limited and it is the heart rate reserve which plays a pivotal role in the haemodynamic adaptation to physical effort. This mechanism becomes particularly important in patients with reduced systolic function because, in addition to the reduced myocardial contractility, stroke volume in HF patients may be further impaired due to significant mitral regurgitation, decreased ventricular compliance, or pericardial constraint. Unfortunately, these patients often present a reduced heart rate reserve, which might limit their ability to adapt to high altitude.…”
Section: Discussionmentioning
confidence: 99%